The role of regulatory T cells and genes involved in their differentiation in pathogenesis of selected inflammatory and neoplastic skin diseases. Part II: The Treg role in skin diseases pathogenesis - Nedoszytko, Bogusław; Lange, Magdalena; Sokołowska-Wojdyło, Małgorzata; Renke, Joanna; Trzonkowski, Piotr; Sobjanek, Michał; Szczerkowska-Dobosz, Aneta; Niedoszytko, Marek; Górska, Aleksandra; Romantowski, Jan; Czarny, Justyna; Skokowski, Jarosław; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Regulatory FOXP3+ T cells (Tregs) constitute 5% to 10% of T cells in the normal human skin. They play an important role in the induction and maintenance of immunological tolerance. The suppressive effects of these cells are exerted by various mechanisms including the direct cytotoxic effect, anti-inflammatory cytokines, metabolic disruption, and modulation of the dendritic cells function. The deficiency of Treg cells number or function are one of the basic elements of the pathogenesis of many skin diseases, such as psoriasis, atopic dermatitis, bacterial and viral infections. They also play a role in the pathogenesis of T cell lymphomas of the skin (cutaneous T cell lymphomas – CTCL), skin tumors and mastocytosis. Here, in the second part of the cycle, we describe dysfunctions of Tregs in selected skin diseases.